Synthesis and structure-activity relationship studies of 1,4-naphthoquinone derivatives as potential anti-trypanosomal agents - Chakaingesu, Chikomborero (Rhodes University, Faculty of Pharmacy, Pharmacy, 2014)
Human African Trypanosomiasis (HAT) is an infectious, vector-borne protozoal disease which is amongst the so-called neglected diseases. In 2000, at a summit of the United Nations, eight Millennium Development Goals (MDGs) were set, to be achieved by 2015. MDG 6 states "to combat HIV/AIDS, malaria & other diseases" . With just under 2 years to go before the end of 2015, HAT is still thriving in developing countries. The drugs currently used for the treatment of HAT are in short supply, have severe side effects and those used to treat late stages of the disease are very difficult to administer. The aforementioned challenges call for research into this neglected disease in order to develop new, safe and easy-to-use medicines. Naphthoquinones are a class of compounds shown to possess anti-parasitic activity, amongst a variety of other biological activities, and therefore this pharmacophore was selected for this study. The purpose of this study was to synthesise derivatives of 2,3-dichloro-1,4- naphthoquinone to be tested for anti-trypanosomal activity and thereafter conduct structureactivity relationship studies. A series of reactions were carried out using thiophenol, phenol and aniline nucleophiles to synthesise thioether (-S-), ether (-O-) and amino (-NH-) derivatives of 2,3-dichloro-1,4-naphthoquinone with various halogen or methyl substituents. Purification of the products was carried out by recrystallisation. Nuclear magnetic resonance (NMR), infra-red (IR) and high pressure liquid chromatography coupled to an electro-spray ionisation mass spectrometer (HPLC-ESI-MS) were the analytical methods used for structural confirmation of the products. There were eighteen 1,4-naphthoquinone derivatives that were successfully synthesised using ethanolic solutions. Unfortunately, attempts to synthesise 1,4-naphthoquinones in reactions involving 2-(trifluoro-methyl)aniline and 2-isopropyl-5-methylphenol were unsuccessful, presumably due to steric hindrance by the bulky ortho-substituents. Although the aims of the synthetic procedures were to obtain both mono- and disubstituted products by nucleophilic displacement of the chlorine atom(s) of 2,3-dichloro-1,4- naphthoquinone, only monosubstituted products were obtained from substitution with aniline and phenol nucleophiles. Thiol nucleophiles, however, selectively yielded disubstituted products only. Synthesised naphthoquinone derivatives were tested against Trypanosoma brucei and calculation of the EC₅₀ values from the obtained dose-response curves was carried out using the four parametric equation. All the 1,4-naphthoquinones showed a degree of potency, except compounds 1b, 3c and 3e, which had little or lack of potency. Structure-activity relationship studies (SARs and QSARs) were carried out to determine which structural features or functional group substituents of the naphthoquinone derivatives contribute or take away from the desired anti-trypanosomal activity. It was found that compounds with the best in vitro anti-trypanosomal potencies in the series of analogous 1,4-naphthoquinone derivatives had EC₅₀ values in the range 2.137 to 2.884 μM. The most potent compound in the series was 2-chloro-3-(4-(trifluoromethyl)phenylamino)-1,4- naphthoquinone 1e; but it was 142-fold less potent than the reference standard of melarsoprol.
Keywords: African trypanosomiasis; Trypanosoma brucei; Naphthoquinone; Protozoan diseases; Drugs -- Structure-activity relationships; Millennium Development Goals